Evaluation of power generation operations in response to changes in surface water reservoir storage - Stillwell, Ashlynn S; Webber, Michael E (Environmental research letters, 2013)
We used a customized, river basin-based model of surface water rights to evaluate the response of power plants to drought via simulated changes in reservoir storage. Our methodology models surface water rights in 11 river basins in Texas using five cases: (1) storage decrease of existing capacity of 10%, (2) storage decrease of 50%, (3) complete elimination of storage, (4) storage increase of 10% (all at existing locations), and (5) construction of new reservoirs (at new locations) with a total increase in baseline reservoir capacity for power plant cooling of 9%. Using the Brazos River basin as a sample, we evaluated power generation operations in terms of reliability, resiliency, and vulnerability. As simulated water storage decreases, reliability generally decreases and resiliency and vulnerability remain relatively constant. All three metrics remain relatively constant with increasing reservoir storage, with the exception of one power plant. As reservoir storage changes at power plants, other water users in the basin are also affected. In general, decreasing water storage is beneficial to other water users in the basin, and increasing storage is detrimental for many other users. Our analysis reveals basin-wide and individual power plant-level impacts of changing reservoir storage, demonstrating a methodology for evaluation of the sustainability and feasibility of constructing new reservoir storage as a water and energy management approach.